Decision Making Towards an Evolutionary Theory of Human Action. - Maldonato, Mauro (Liverpool University Press, 2010)
Interprets the secular controversy about the nature of human decision-making in light of discoveries in cognitive neurosciences and research in neuroeconomics and neuroethics. This book provides the readers with the means to view and assess personal decision-making and resultant action in a different way.